Pendidikan Multikultural sebagai Strategi Penguatan Moderasi Beragama di Indonesia melalui Systematic Literature Review - Ida Ayu Gede Prami Astiti; Dewa Bagus Sanjaya; I Nengah Suastika (Varied Knowledge Journal, 2026)
Multicultural education plays a strategic role in fostering tolerance and respect for diversity within Indonesia’s plural society. Amid the increasing challenges of intolerance and radicalism, strengthening religious moderation has become an urgent priority in the education sector. This study aims to analyze the role of multicultural education as a strategy for strengthening religious moderation in Indonesia through a Systematic Literature Review (SLR) approach. The study reviewed relevant scholarly articles from accredited national and reputable international journals through stages of identification, screening, eligibility, and inclusion. The findings indicate that multicultural education contributes significantly to the development of tolerance, inclusivity, and mutual respect among religious communities. The integration of multicultural values into curricula and learning practices also encourages students to develop moderate and inclusive religious perspectives. However, its implementation still faces challenges, including limited educator understanding, inadequate curriculum support, and insufficient social environmental support. Therefore, strengthening educational policies, improving educator capacity, and systematically integrating religious moderation values into learning processes are essential. This study contributes to the development of inclusive educational policies and practices that support diversity and social harmony.